Extreme Rainfall Indices for Tropical Monsoon Countries in Southeast Asia - Kusumastuti, C.; Weesakul, S. (Institute of Research and Community Outreach - Petra Christian University, 2014)
Southeast Asian countries have the possibility to have rainfall and number of extreme rainfall event change due to future climate variation. This paper proposed three extreme rainfall indices as a modification of climate extremes indices from CLIMDEX Project by researchers at the Climate Change Research Centre (CCRC), the University of New South Wales (UNSW). The proposed indices aim to be used as a parameter for observing extreme rainfall events in tropical monsoon countries. Eleven extreme precipitation indices from CLIMDEX Project and the three proposed extreme precipitation for tropical monsoon countries are systematically analyzed based on data of daily rainfall from meteorological stations in Bangkok and Jakarta. Mann-Kendall test was used to observe the trend of extreme rainfall. In general, the analysis of a total of 14 extreme indices show both Bangkok and Jakarta received more rainfall during rainy season and less rainfall during dry season. Specifically, a significant increasing trend of extreme rainfall indices (R60 and R80) was revealed using the proposed indices.